CHARACTERISTICS OF ALLAMANDA FLOWER (Allamanda cathartica L.) ETHANOLIC EXTRACT - Suci Rahmawati; Ayu Ovia Riski; Nova Yustisla; Yetti Purnama (Poltekkes Kemenkes Bengkulu, 2022)
Allamanda flowers were known as ornamental plants, but also have benefits as traditional medicine. Phytochemical screening is an important first step in identifying potential secondary metabolites of a plant. This study were to determine of characteristics and phytochemical screening of allamanda flowers ethanolic extract. Allamanda flowers used were natural flowers that have been air-dried for 7 days. The extract from dry sample of allamanda flowers was obtained by maceration method using 96% ethanol as solvent. The extracts were evaluated their characteristics including, yield, ash content, water content and phytochemical screening by color reaction method with specific reagent. The results were obtained that extract characteristics, namely the yield of 51.77%; water content of 1.14%; and ash content of 4.71%. The results were obtained from the phytochemical test that 96% ethanol extract of allamanda flowers contains flavonoid and saponin. It can be concluded that ethanol extract of allamanda flowers with ash content of 4.71% and water content of 1.14% contains flavonoids and tannins.